Cumulative plasma effects in cavity-enhanced high-order harmonic generation in gases - Saule, Tobias; Hoegner, Maximilian; Lilienfein, Nikolai; De Vries, Oliver; Ploetner, Marco; Yakovlev, Vladislav S.; Karpowicz, Nicholas; Limpert, Jens; Pupeza, Ioachim (APL Photonics, 2018)
Modern ultrafast laser architectures enable high-order harmonic generation (HHG) in gases at (multi-) MHz repetition rates, where each atom interacts with multiple pulses before leaving the HHG volume. This raises the question of cumulative plasma effects on the nonlinear conversion. Utilizing a femtosecond enhancement cavity with HHG in argon and on-axis geometric extreme-ultraviolet (XUV) output coupling, we experimentally compare the single-pulse case with a double-pulse HHG regime in which each gas atom is hit by two pulses while traversing the interaction volume. By varying the pulse repetition rate (18.4 and 36.8 MHz) in an 18.4-MHz roundtrip-frequency cavity with a finesse of 187, and leaving all other pulse parameters identical (35-fs, 0.6-μJ input pulses), we observe a dramatic decrease in the overall conversion efficiency (output-coupled power divided by the input power) in the double-pulse regime. The plateau harmonics (25-50 eV) exhibit very similar flux despite the twofold difference in repetition rate and average power. We attribute this to a spatially inhomogeneous plasma distribution that reduces the HHG volume, decreasing the generated XUV flux and/or affecting the spatial XUV beam profile, which reduces the efficiency of output coupling through the pierced mirror. These findings demonstrate the importance of cumulative plasma effects for power scaling of high-repetition-rate HHG in general and for applications in XUV frequency comb spectroscopy and in attosecond metrology in particular.
CRIS-Team Scopus Importer:2023-04-20